2008
DOI: 10.1007/s10461-008-9449-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Among HIV Positive New Yorkers: Prevalence, Frequency, and Opportunities for Cessation

Abstract: Tobacco use presents unique health risks for persons living with HIV/AIDS (PLWHA). There is an urgent need to characterize tobacco use among PLWHA, and to assess the capacity of HIV/AIDS service providers to deliver smoking cessation interventions. Questionnaires were administered to PLWHA in care in New York State (n = 1,094) and to State-funded HIV/AIDS service providers (n = 173) from 2005 to 2007. Current PLWHA smoking prevalence was 59%, three times the general population rate. Over 50% of current smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
225
9
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(253 citation statements)
references
References 35 publications
16
225
9
3
Order By: Relevance
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
See 3 more Smart Citations
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
“…32 Further, there is evidence that a majority of HIV health care providers advise their patients to quit smoking, but these interventions are not universal. 4,5 Among those who provide cessation services, the most frequent interventions include brief advice to quit, recommending nicotine replacement, and providing print self-help materials. 32 Treatment providers cite both patient resistance to smoking cessation interventions, as well as systemic barriers (eg, lack of reimbursement for pharmacotherapy, lack of time, and lack of provider confidence in their abilities to provide smoking cessation) as barriers to effective implementation of smoking cessation treatments in HIV care.…”
Section: Smoking Cessation Efforts In Community Treatment Of Hiv/aidsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,24 Current smoking has been reported in 40% to 70% of HIV-positive patients, two-to three-fold greater than the general population. 4,22,[25][26][27][28][29][30][31] Compared with non-smokers, smokers have a two-fold or greater increased risk of MI 19 and CVD. 24,32 Although two studies have reported decreasing rates of smoking over time, in part suggesting that in an aging cohort, smoking rates are decreasing, 4,5 few data are available on actual rates of smoking as HIV-positive patients age.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%